Grimm. Season six [videorecording (DVD)] - Carpenter, Stephen (Screenplay author); Greenwalt, David; Kouf, Jim (Universal Pictures Home Entertainment, 2017)
Now that the nefarious forces of Black Claw have been silenced, Nick faces an all too familiar foe in Captain Sean Renard. Having gained a seat of power as the mayor elect of Portland, Renard is poised to bring rise to his own brand of law and order. Nick must take a stand to protect his city and those closest to him, especially his child with Adalind. It will take the full force of Nick and his allies to find a way to bring peace.